1999
DOI: 10.4269/ajtmh.1999.60.927
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a long-term effect of a single dose of praziquantel on Schistosoma mansoni-induced hepatosplenic lesions in northern Uganda.

Abstract: Abstract. Treatment with praziquantel reduces the prevalence and intensity of Schistosoma mansoni infection. However, reversibility of periportal fibrosis of the liver, which potentially leads to fatal complications, is not unequivocally substantiated. In the Nile District of Uganda, 460 patients were parasitologically (Kato-Katz method) and ultrasonographically examined during

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…36 An important unmeasured confounder could be secular changes in the exposure to, as well as potential treatment of, malaria infections, which influence both Hb and splenomegaly. 5 However, our study presented plausible evidence of the impact of the intervention since we observed significant changes in infection and morbidity in randomly sampled children in 37 schools across different transmission settings in the country, after adjusting estimates for age and sex differences and potentially confounding variables. Additionally, there was a close agreement between the observed impact and mathematical model predictions of programme effectiveness.…”
Section: Limitations and Plausibilitymentioning
confidence: 71%
See 1 more Smart Citation
“…36 An important unmeasured confounder could be secular changes in the exposure to, as well as potential treatment of, malaria infections, which influence both Hb and splenomegaly. 5 However, our study presented plausible evidence of the impact of the intervention since we observed significant changes in infection and morbidity in randomly sampled children in 37 schools across different transmission settings in the country, after adjusting estimates for age and sex differences and potentially confounding variables. Additionally, there was a close agreement between the observed impact and mathematical model predictions of programme effectiveness.…”
Section: Limitations and Plausibilitymentioning
confidence: 71%
“…Clinical trials have demonstrated that praziquantel is a safe and efficacious treatment against both species, and that repeated chemotherapy decreases infection and related morbidity. [1][2][3][4][5][6][7] One of the main control methods is treating schoolchildren with praziquantel together with albendazole as part of school health programmes. As this method uses the existing school infrastructure and provides easy accessibility to children, it is a cost-effective public health strategy, 8 and many pilot programmes have demonstrated its feasibility, affordability and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…47,48 The current study complements and expands previous ultrasonography-based studies within Africa on a number of issues. First, although previously published surveys 17,[49][50][51][52][53][54] have used ultrasongraphy to measure schistosomiasisassociated morbidity both in children and in adults, which is indicative of long-term chronic infections, we assessed ultrasonography in monitoring schistosomiasis morbidity in control programs focused on children. Although we recognize that measuring only children might be a limitation, if one considers the overall aim of this study, our results still contribute to assessing the suitability of ultrasonography for more recent infections and targeting age groups for future disease control programs.…”
Section: Discussionmentioning
confidence: 99%
“…A rate of nearly 30% was reported from one stretch of the river (Nelson, reported in WHO, 1987). Along another part of the river, a prevalence of over 80% was found in the early 1990s, but this declined to 30% following treatment with praziquantel (Frenzel et al, 1999;Odongo-Aginya et al, 2002). Similar figures were again reported for the same area of the Nile between 2005(Odongo-Aginya et al, 2010.…”
Section: Introductionmentioning
confidence: 99%